People with Disabilities in Qatar: Empowerment, Aspirations, and Society’s Behaviour Influences - Alkahlout, Ola; Aljomaa , Noura (The Center for Disability Studies and Services Brawijaya University, 2023)
People with disabilities have become a critical, international phenomenon. People with disabilities are those who have a physical or mental condition which limits their movements, senses, or activities. This article is a discussion of the factors which influence the empowerment of Qatari people with disabilities. The Qatari government has gone a long way towards making people with disabilities valued and appreciated by providing opportunities for education and work. Qataris are also keen to apply the literal teachings of Islam, although Qatar’s tribal culture has an effective influence in dealing with people with disabilities. The analysis of the findings from the interviews with charitable organisations’ staff members showed that Qatari people with disabilities still lack the empowerment to achieve their aims of being productive members of society. People with disabilities in Qatar desire a decent life which meets their basic needs such as healthcare, education, and job opportunities.